The Application of Financial Recording Applications Towards Financial Report for Micro, Small and Medium Enterprises - Finna Afrilia Elmanda; Gusnerlisa Gita Merdikawati; Ratih Wahyuni (International Journal of Research and Applied Technology (INJURATECH), 2022)
In this current era, many Micro, Small and Medium Enterprises (MSMEs) have started to use financial report recording applications in recording incoming and outgoing financial reports. This research aims to determine how much application of financial statement recording applications in making financial reports on Micro, Small and Medium Enterprises (MSMEs) using an android based financial recording application. This study uses descriptive quantitative research methods using data collection techniques in the form of questionnaires. The results of this study explain that the role of using applications to record financial reports for Micro, Small and Medium Enterprises has a positive impact on the sustainability of a business. By using an android-based financial recording application, it can make it easier to record financial reports and minimize errors in recording. Therefore, this research benefits Micro, Small and Medium Enterprises actors to understand better and understand technology so that they can apply financial statement recording applications properly.